Compression techniques for arbitrary support shape - Ng, Wee Kok. (2008)
This research aims at exploiting compression techniques for non-uniform (arbitrarily shaped) images. One coding technique that has been included in the MPEG-4 is the shape Adaptive Discrete Cosine Transform (SA-DCT), which is first proposed by Sikora and Makai in 1995. It can be easily incorporated into existing block-based coding schemes.